2018
DOI: 10.1016/j.envpol.2018.09.123
|View full text |Cite
|
Sign up to set email alerts
|

Short- and medium-chain chlorinated paraffins in sediments from the Laizhou Bay area, North China: Implications for transportation from rivers to marine environment

Abstract: The concentrations of short-and medium-chain chlorinated paraffins (SCCPs and MCCPs) were measured for riverine and marine sediments from the Laizhou Bay area in order to investigate their spatial distributions, possible sources and transport behaviors. Concentrations of SCCPs and MCCPs in riverine sediments varied from 8.4 to 2000 ng g À1 dw and from 1.8 to 3200 ng g À1 dw, respectively. Higher concentrations were found exclusively at industrial sites. Emissions from local factories were the main source of CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
5
20
0
Order By: Relevance
“…In the aquatic environment, SCCPs are more likely to be adsorbed in sediment since they have low water solubility and high carbon partition coefficients (Environment Canada 2008). There are quite a number of studies that have been reported globally (Wang et al 2019a;Pan et al 2018;Pan et al 2020;Huang et al 2019a;Wang et al 2020a;Labadie et al 2019).…”
Section: Aquatic Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aquatic environment, SCCPs are more likely to be adsorbed in sediment since they have low water solubility and high carbon partition coefficients (Environment Canada 2008). There are quite a number of studies that have been reported globally (Wang et al 2019a;Pan et al 2018;Pan et al 2020;Huang et al 2019a;Wang et al 2020a;Labadie et al 2019).…”
Section: Aquatic Environmentmentioning
confidence: 99%
“…Thus, Shanghai aquatic system is mainly contaminated by MCCPs than SCCPs. Another study by Pan et al (2018) determined SCCP concentration in sediments from industrial, urban and rural areas of the Laizhou Bay, North China, from 14 September 17 to October 2009. SCCP concentration ranged from 8.4 to 2000 ng g −1 with ∑SCCP concentration of 160 ng g −1 dw.…”
Section: Sedimentmentioning
confidence: 99%
“…All the samples were corrected by blanks, but not by surrogate recoveries. Detailed information about the analytical method is described in the supplementary information and in our latest study (Pan et al, 2018).…”
Section: Qa/qcmentioning
confidence: 99%
“…CPs are commonly used as additives in the rubber industry, such as in marine coatings, rubber tires, and polyurethane materials (Tong et al, 2003;Wei et al, 2016). Many researchers have reported that compared to SCCPs, MCCPs are more prone to be adsorbed onto particles and settle in sediment instead of being transported by water over long distance (Chen et al, 2011;Ma et al, 2014;Pan et al, 2018;Zeng et al, 2013a). Thus, the mooring fishing boats might be a major contributor to MCCPs in the Xiaoqing River.…”
Section: Cps In Sediments Of the Xiaoqing River And Laizhou Baymentioning
confidence: 99%
See 1 more Smart Citation